Therapeutic Potential of Mesenchymal Stem Cells in Regenerative Medicine - Devang M. Patel; Jainy Shah; Anand S. Srivastava (Stem Cells International)
Mesenchymal stem cells (MSCs) are stromal cells that have the ability to self-renew and also exhibit multilineage differentiation into both mesenchymal and nonmesenchymal lineages. The intrinsic properties of these cells make them an attractive candidate for clinical applications. MSCs are of keen interest because they can be isolated from a small aspirate of bone marrow or adipose tissues and can be easily expanded in vitro. Moreover, their ability to modulate immune responses makes them an even more attractive candidate for regenerative medicine as allogeneic transplant of these cells is feasible without a substantial risk of immune rejection. MSCs secrete various immunomodulatory molecules which provide a regenerative microenvironment for a variety of injured tissues or organ to limit the damage and to increase self-regulated tissue regeneration. Autologous/allogeneic MSCs delivered via the bloodstream augment the titers of MSCs that are drawn to sites of tissue injury and can accelerate the tissue repair process. MSCs are currently being tested for their potential use in cell and gene therapy for a number of human debilitating diseases and genetic disorders. This paper summarizes the current clinical and nonclinical data for the use of MSCs in tissue repair and potential therapeutic role in various diseases.